ALIRAN KALAM SALAFIYAH: Studi atas Perkembangan Pemikirannya - Darwin Agung Septian Miolo; Muhammad Arif (Farabi, 2021)
This article aims to reveal how the Kalam Salafiyah flow and how its thinking develops. The method used is descriptive qualitative analysis method. The results of the study and discussion show that the kalam salafiyah flow has several characteristics as stated by Ibrahim Madzkur, namely: first, they prioritize history (naqli) rather than merayah (aqli); second, in matters of religion and in matters of religious branches, it only starts from the explanation of the al-Kitab and as-Sunnah; third, they believe in Allah without further contemplation (Essence of Allah) and do not have anthromophism (equating Allah with creatures); fourth, interpret the verses of the al-Qur'an according to the meaning of their birth and do not attempt to translate them. Ibn Taymiyyah argues that the salaf people are those who think that there is no way to know the creed, the law, and what both of them have to do with it, nothing but based on the Qur'an and Hadith. The Salaf accept all the information contained in the Qur'an and Hadith. Refusing means releasing the rope of religion. Intellect does not have the power to interpret, interpret, or punish the Qur'an. Intellect is only able to justify, obey, and explain the approach between the arguments of reason (contextual), the arguments of the Qur'an and the Hadith (textual) with no difference between the arguments of reason with the arguments of the Qur'an and the Hadith. Intellect has the position of being a witness, not a judge, as an enforcer and not an opponent, as an explanation for the arguments contained in the al-Qur'an. Salaf people always make sense behind al-Qur'an and Hadith.